Effect of Mordanting Method on Fabric Color Quality Using Red Melinjo (Gnetum gnemon L.) Peel Extract - Jasmine Kalila; Sugiyem (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study investigates the effect of three mordanting methods (pre-, simultaneous, and post-mordanting) on the color fastness quality of shantung and Japanese cotton fabrics dyed with red melinjo peel extract (Gnetum gnemon L.). A 2×3 factorial experimental design was employed, and data were analyzed using the Kruskal-Wallis test at the 5% significance level. Results showed significant differences between mordanting methods (p=0.004). For washing fastness, simultaneous mordanting yielded optimal results (mean score: 4 for shantung, 4.5 for Japanese cotton), while post-mordanting showed the lowest performance. For sunlight fastness, pre- and post-mordanting achieved good results (4.5) on shantung fabric, whereas simultaneous mordanting demonstrated the best performance (5) on Japanese cotton. The novelty of this research lies in the use of underutilized red melinjo peel waste as a sustainable textile dye source and in providing the first comprehensive evaluation of the effects of mordanting methods on its colorfastness performance. This study demonstrates that red melinjo peel extract has significant potential as an environmentally friendly natural textile dye, with its effectiveness strongly influenced by the selection of mordanting technique.